Meta-Analysis of Associations between Maternal Age, Low Hemoglobin Level during Pregnancy, Low Birth Weight, and Preterm Birth - Kusumawati, Ima; Murti, Bhisma; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2023)
Background: Maternal age <19 years and anemia in pregnancy are often associated with adverse neonatal outcomes. This study aims to analyze the relationship between maternal age <19 years and anemia in pregnancy (Hb <11 g/dL) on the incidence of low birth weight babies (LBW) and premature birth. Subjects and Method: The research meta-analysis took cohort studies published in 2018-2022. The PICO formulation used: the population is pregnant women, the intervention consists of groups of pregnant women aged <19 years and pregnant women with anemia (Hb<11 gr/dL), comparison is the group of pregnant women aged 20-35 years and pregnant women are not anemic while Outcomes were LBW and premature birth. Search articles through databases: PubMed, springer, science direct and google scholar with the keywords “Adolescence pregnancy OR young OR Teenage AND Pregnancy AND neonatal outcome OR Low birth weight OR preterm birth OR Low weight”, “Anemia OR Maternal anemia AND Neonatal outcome OR Preterm birth". Data analysis using the Review Manager (RevMan) 5.4 application. Results: A total of 7 cohort articles on pregnancy aged <19 years and 5 cohort articles on anemia were analyzed. Articles come from Canada, Turkey, England, Russia, Finland, China, Chinese Taipei, Ethiopia, Zambia and Bangladesh. The sample sizes were n=43,399 (maternal age and LBW), n=55,049 (maternal age with premature birth), n=16,544,075 (anemia and premature birth). Pregnant women aged <19 years have a 1.63 risk of giving birth to LBW babies (aOR= 1.63; 95% CI= 0.96 to 2.78; p= 0.070) and 1.41 times giving birth to premature babies (aOR= 1.41; 95% CI= 0.78 to 2.56; p= 0.250). Pregnant women with anemia have a 1.60 times risk of giving birth to premature babies (aOR= 1.60; 95% CI= 1.10 to 2.32; p= 0.010). Conclusion: The age of pregnant women <19 years does not have a significant effect on the occurrence of LBW and premature birth. Pregnant women with anemia increase the risk of premature birth. Keywords: Maternal age, anemia, low birth weight, premature birth Correspondence: Ima Kusumawati. Master's Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36A, Surakarta 57126, Central Java, Indonesia. Email:Ima.kusumawati@student.uns.ac.id Mobile: +6285740839246